Conformational and charge changes induced by l-Arginine and l-lysine increase the solubility of chicken myosin. (April 2019) - Li, Shiyi; Li, Linxian; Zhu, Xiaoxu; Ning, Cheng; Cai, Kezhou; Zhou, Cunliu
Abstract: The paper investigated the mechanism thatl -arginine (Arg)/l -lysine (Lys) affected myosin solubility by spectroscopic technologies and chemical probes. The results showed that Arg and Lys increased myosin solubility. However, neither Arg, nor Lys changed the Raman pattern of myosin. Raman spectra disclosed that Arg and Lys decreased the intensity at 753 cm −1, but increased the intensity at 1, 234, 1, 448, and 2934 cm −1 and the I853/830 and I3287/3443 ratio, and caused a red-shift at 1656 and 2934 cm −1 . Fluorescence spectra showed that Arg/Lys caused the reduced intensity and red-shift peak position of myosin. Arg and Lys slightly affected total reactive sulfhydryl content, increased the ANS-based hydrophobicity and reactive sulfhydryl content, but decreased the PRODAN-based hydrophobicity. Our results collectively demonstrated that Arg and Lys induced myosin to partially unfold and gain more negative charges, which overall enhanced the interaction between myosin and water, ultimately contributing to the increased solubility of myosin. Graphical abstract: Highlights: Neither arginine, nor lysine changed the Raman patterns of myosin. The intensity of Raman bands raised at 1448 and 2934 cm −1 but abated at 753 cm −1 . Arginine/lysine increased the I853/830 and I3287/3443 ratio of myosin. Lysine caused the low intensity and red-shift fluorescence peak position of myosin. Arginine/lysine abated the PRODAN-based hydrophobicity but raised myosin solubility.